Pendugaan Umur Simpan Daun Bawang (Allium Fistulosum L.) Terolah Minimal menggunakan Metode ASLT (Accelerated Shelf Life Test) Model Arrhenius - Ariesta, Irenna Putri; Syska, Kavadya; Nurhayati, Asti Dewi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Minimal processing of green onions (Allium fistulosum L.) have become increasingly popular in the food industry. The minimal processing method offers advantages in preserving the nutritional and organoleptic characteristics of green onions. However, quality changes during storage pose a significant challenge in ensuring sustainability and product quality. This research aims to 1) assess the quality changes in minimally processed green onions using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius model, and 2) determine the shelf life of minimally processed green onions using the ASLT method with the Arrhenius model. The ASLT method was applied with accelerated storage temperature variations to hasten the quality changes in the product. The Arrhenius model was employed to analyze the kinetics of reactions occurring during accelerated storage, providing an accurate prediction of the shelf life. Shelf life estimation was conducted using green onions packaged in plastic wrapping, HDPE plastic, and PP plastic, stored at temperatures of 10°C and 30°C for 9 days with observations every 3 days. Data were analyzed using ANOVA (Analysis of Variance) with a 5% confidence level. If the ANOVA results indicated significant differences, the Honest Significant Difference (HSD) test was performed. The research results showed that at 10°C, green onions stored in plastic wrap packaging exhibited the highest level of damage compared to HDPE and PP packaging. Meanwhile, at 30°C, minimally processed green onions in HDPE packaging experienced the highest level of damage compared to plastic wrap and PP packaging. The shelf life estimation using the ASLT method with the Arrhenius model indicated that the shelf life of green onions in wrapping packaging at 10°C tends to be longer compared to other packaging methods. These findings provide insights into the stability of minimally processed green onion products and lay the foundation for the development of optimal storage strategies. The application of ASLT with the Arrhenius model can assist the food processing industry in improving efficiency and product quality, particularly for minimally processed green onion products.